The role of cholesterol on the activity and stability of neurotensin receptor 1. - Oates, J; Faust, B; Attrill, H; Harding, P; Orwick, M; Watts, A (2012)
Understanding the role of specific bilayer components in controlling the function of G-protein coupled receptors (GPCRs) will be a key factor in the development of novel pharmaceuticals. Cholesterol-dependence in particular has become an area of keen interest with respect to GPCR function; not least since the 2.6Å crystal structure of the β2 adrenergic receptor revealed a putative cholesterol binding motif conserved throughout class-A GPCRs. Furthermore, experimental evidence for cholesterol-dependent GPCR function has been demonstrated in a limited number of cases. This modulation of receptor function has been attributed to both direct interactions between cholesterol and receptor, and indirect effects caused by the influence of cholesterol on bilayer order and lateral pressure. Despite the widespread occurrence of cholesterol binding motifs, available experimental data on the functional involvement of cholesterol on GPCRs are currently limited to a small number of receptors. Here we investigate the role of cholesterol in the function of the neurotensin receptor 1 (NTS1) a class-A GPCR. Specifically we show how cholesterol, and the analogue cholesteryl hemisuccinate, influence activity, stability, and oligomerisation of both purified and reconstituted NTS1. The results caution against using such motifs as indicators of cholesterol-dependent GPCR activity.